FOSTERING CREATIVITY AND UNDERSTANDING OF ART: COMMUNITY DEVELOPMENT FOR NASYATUL AISYIYAH MUNGKA CHILDREN THROUGH THE USE OF INFORMATION TECHNOLOGY IN ARTS LEARNING - Maryelliwati Maryelliwati; Harizqi Azri; Hari Adi Rahmad; Wahyudi Rahmat; Rival Yuhendri (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2023)
This initiative is designed to enhance the comprehension of Nasyatul Aisyiyah Mungka children, emphasizing that subjects like arts or sciences should be approached with conceptual understanding rather than mere memorization. The service activity unfolds in stages, beginning with the presentation of materials and followed by practical demonstrations and simple simulations facilitated by evolving technology. The core principle involves involving Nasyatul Aisyiyah Mungka's children in applying discussed arts concepts. Additionally, simulations are presented to encourage them to recognize the connection between their daily activities and the realms of arts or sciences. The methodology includes pretests, interviews (focus group discussions), concept delivery, experimental studies (using props and practical activities), and post-tests. The pretest results yielded a mean score of 53.83, while after the service activities, the posttest results indicated an increased mean score of 69.16. This service activity integrates not only one scientific field but a fusion of arts and engineering, where the emphasis on art science is prioritized for conceptual understanding. Simultaneously, engineering science concentrates on design effectiveness, encompassing assembly, installation, and experimentation with props and simulations. This interdisciplinary approach contributes to an enhanced understanding, evidenced by the elevated posttest scores.